2022
DOI: 10.3389/fpls.2021.812396
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Watermelon Onto Pumpkin Increases Chilling Tolerance by Up Regulating Arginine Decarboxylase to Increase Putrescine Biosynthesis

Abstract: Low temperature is a major environmental factor that severely impairs plant growth and productivity. Watermelon (Citrullus lanatus) is a chilling-sensitive crop. Grafting of watermelon onto pumpkin rootstock is an effective technique to increase the chilling tolerance of watermelon when exposure to short-time chilling stress. However, the mechanism by which pumpkin rootstock increases chilling tolerance remains poorly understood. Under 10°C/5°C (day/night) chilling stress treatment, pumpkin-grafted watermelon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Grafting can alter secondary metabolite accumulation, impacting scion growth, quality, and stress tolerance [18,[56][57][58][59][60]. Strong rootstocks were used to enhance the resistance of scions, using rootstocks to enhance the disease resistance of potatoes, using pumpkin as rootstock to enhance the cold resistance of cucumber and watermelon scions, by upregulating the key genes in the carbon fixation, photosynthesis, and polyamine metabolism pathway [61,62]. By overexpressing the key gene, MdFRK2, of sugar metabolism in the apple rootstock, drought resistance was improved [63].…”
Section: Discussionmentioning
confidence: 99%
“…Grafting can alter secondary metabolite accumulation, impacting scion growth, quality, and stress tolerance [18,[56][57][58][59][60]. Strong rootstocks were used to enhance the resistance of scions, using rootstocks to enhance the disease resistance of potatoes, using pumpkin as rootstock to enhance the cold resistance of cucumber and watermelon scions, by upregulating the key genes in the carbon fixation, photosynthesis, and polyamine metabolism pathway [61,62]. By overexpressing the key gene, MdFRK2, of sugar metabolism in the apple rootstock, drought resistance was improved [63].…”
Section: Discussionmentioning
confidence: 99%
“…Grafting is one of the most commonly used techniques in vegetable crop production, which can improve stress tolerance, yield, and quality of vegetables ( Shi et al, 2019 ; Wei et al, 2019 ; Darre et al, 2022 ). In recent years, many studies have shown that the cold tolerance of vegetable crops can be improved by grafting onto tolerant rootstock by maintaining higher photosynthesis, enhancing antioxidant activity to scavenge excess reactive oxygen species (ROS) ( Xu et al, 2016 ; Lu J. et al, 2022 ; Luan et al, 2022 ), but information regarding the molecular mechanism of grafting in increasing cold tolerance remains largely unknown. In this study, we found that cucumber seedlings grafted onto figleaf gourd significantly increased the tolerance to cold stress through promoting the accumulation of ABA to induce the expression of WRKY41 and WRKY46 , which further activated the expression of miR396b-5b to target cleavage of TPR .…”
Section: Discussionmentioning
confidence: 99%
“…Grafting is an important agronomic technology to improve the quality traits and/or tolerance of scions to environmental stresses. Enhanced cold tolerance of grafted seedlings has been accomplished recently in watermelon ( Citrullus lanatus ) and cucumber ( Cucumis sativus ), respectively ( Lu et al 2022 ; Sun et al 2022 ). Actually, grafting with grapevine rootstocks could promote expression of numerous TFs and accumulation of stilbene, flavonol, and ABA in scions ( Chitarra et al 2017 ; Zhang et al 2022a ).…”
Section: Approaches To Improve Cold Tolerance In Grapevinementioning
confidence: 99%